2016
DOI: 10.1002/bit.26185
|View full text |Cite
|
Sign up to set email alerts
|

Glucose oxidase stabilization against thermal inactivation using high hydrostatic pressure and hydrophobic modification

Abstract: High hydrostatic pressure (HHP) stabilized glucose oxidase (GOx) against thermal inactivation. The apparent first-order kinetics of inactivation of GOx were investigated at 0.1-300 MPa and 58.8-80.0°C. At 240 MPa and 74.5°C, GOx inactivated at a rate 50 times slower than at atmospheric pressure at the same temperature. The apparent activation energy of inactivation at 300 MPa was 281.0 ± 17.4 kJ mol or 1.3-fold smaller than for the inactivation at atmospheric pressure (378.1 ± 25.6 kJ mol ). The stabilizing ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
(148 reference statements)
2
6
1
Order By: Relevance
“…The apparent E ai at 0.1 MPa (167 kJ mol −1 ) was 3.2 times smaller than the apparent E ai at 150 MPa (532 kJ mol −1 ). This contrasts the results of XOx (Halalipour et al, 2017a) and GOx (Halalipour et al, 2017b) which reported a decrease in E ai with increased pressure. However, the labile fraction of AOx from Pichia pastoris followed a similar trend as GaOx (Buchholz-Afari et al, 2019).…”
Section: Activation Energy and The Effect Of Temperature On K Inactcontrasting
confidence: 99%
See 2 more Smart Citations
“…The apparent E ai at 0.1 MPa (167 kJ mol −1 ) was 3.2 times smaller than the apparent E ai at 150 MPa (532 kJ mol −1 ). This contrasts the results of XOx (Halalipour et al, 2017a) and GOx (Halalipour et al, 2017b) which reported a decrease in E ai with increased pressure. However, the labile fraction of AOx from Pichia pastoris followed a similar trend as GaOx (Buchholz-Afari et al, 2019).…”
Section: Activation Energy and The Effect Of Temperature On K Inactcontrasting
confidence: 99%
“…The effect of pressure on k inact of GaOx at each temperature is represented in Figure 2 (Halalipour et al, 2017a), GOx (Halalipour et al, 2017b), AOx (Buchholz-Afari et al, 2019 and a pectinase cocktail (Tomlin et al, 2013), which were 9.5-28.9 cm 3 mol −1 , 22.8-57.0 cm 3 mol −1 , and 13.7-33.7 cm 3 mol −1 , respectively. A greater ΔV ‡ corresponds to a greater stabilizing effect of pressure is; therefore, pressure has a stronger stabilization effect on GaOx than on other reported enzymes.…”
Section: Activation Volume and The Role Of Cavitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid advances in the understanding of molecular interactions, [1][2][3][4] development of novel materials, [5][6][7][8][9][10] and stabilization of biologically active compounds [11][12][13] is increasing the scope for practical electroanalytical tools in the field. 14,15 These advances coupled with simple electrochemical techniques are especially compelling for diagnostic applications related to food, 4,6,7,[16][17][18][19][20][21] agriculture, 16,[22][23][24][25][26][27][28] and the environment 22,[28][29][30][31] that are highly sensitive to cost.…”
mentioning
confidence: 99%
“…It should be noted that small changes in unfolding temperature can correlate to very large differences in stability at a given temperature. Although the thermal unfolding of all the GOx samples is irreversible, the DSC scans can still be fitted with a model, indicating independent two-state transitions (native to unfolded). , Figure shows the buffer-subtracted DSC scans of unmodified GOx, SENs, and cross-linked SENs after normalization using the GOx concentration. The enthalpy and temperature of the denaturation are summarized in Table .…”
Section: Results and Discussionmentioning
confidence: 99%